Inversion of force lines in fiber-reinforced jammed granular material - Iliev, Pavel S. (Eur Phys J E Soft Matter, 2021)
ABSTRACT: Freestanding columns, built out of nothing but loose gravel and continuous strings can be stable even at several meters in height and withstand vertical loads high enough to severely fragment grains of the column core. We explain this counter-intuitive behavior through dynamic simulations with polyhedral rigid particles and elastic wire chains. We evaluate the fine structure of the particle contact networks, as well as confining forces and reveal fundamental intrinsic differences to the well-studied case of confining silos. GRAPHIC ABSTRACT: [Image: see text]